Profile of Adenosine Deaminase (ADA) Level in Active Pulmonary Tuberculosis Patients - Sheila Gerhana Darmayanti; Soedarsono Soedarsono (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Pulmonary tuberculosis (TB) has a risk of increasing the transmission of infection and death may occur if diagnosis is delayed due to limited testing. Faster, more accurate, inexpensive new methods with easy-to-obtain samples, such as serum levels of Adenosine deaminase (ADA), need to be applied. This study aims to compare serum ADA levels in new cases of pulmonary TB patients and in healthy individuals, and to examine the potential of serum ADA to diagnose pulmonary TB. Methods: This study was an observational analytic study conducted at the Outpatient Clinic of TB/TB-MDR-DOTS, Dr. Soetomo Hospital, Surabaya, Indonesia, from August to December 2019. The subjects were new cases of pulmonary TB patients and healthy individuals. Serum ADA levels were analyzed using the enzymatic colorimetric method, using Erba XL 600. Results: A total of 60 patients were divided into 34 new cases of pulmonary TB patients and 26 healthy individuals. Serum ADA levels in new cases of pulmonary TB patients were significantly higher compared to those in healthy individuals (P<0.001). The cut-off value of serum ADA levels was 11.4 U/L with a sensitivity of 85.3% and specificity of 84.6%. Conclusion: ADA serum levels are increased in patients with new cases of pulmonary TB. ADA serum can be used to assist the diagnosis of tuberculosis.